Biocatalytic Oxidative Cascade for the Conversion of Fatty Acids into α‐Ketoacids via Internal H2O2 Recycling. Issue 2 (6th December 2017) - Gandomkar, Somayyeh; Dennig, Alexander; Dordic, Andela; Hammerer, Lucas; Pickl, Mathias; Haas, Thomas; Hall, Mélanie; Faber, Kurt
Abstract: The functionalization of bio‐based chemicals is essential to allow valorization of natural carbon sources. An atom‐efficient biocatalytic oxidative cascade was developed for the conversion of saturated fatty acids to α‐ketoacids. Employment of P450 monooxygenase in the peroxygenase mode for regioselective α‐hydroxylation of fatty acids combined with enantioselective oxidation by α‐hydroxyacid oxidase(s) resulted in internal recycling of the oxidant H2 O2, thus minimizing degradation of ketoacid product and maximizing biocatalyst lifetime. The O2 ‐dependent cascade relies on catalytic amounts of H2 O2 and releases water as sole by‐product. Octanoic acid was converted under mild conditions in aqueous buffer to 2‐oxooctanoic acid in a simultaneous one‐pot two‐step cascade in up to >99 % conversion without accumulation of hydroxyacid intermediate. Scale‐up allowed isolation of final product in 91 % yield and the cascade was applied to fatty acids of various chain lengths (C6:0 to C10:0). Abstract : An atom‐efficient biocatalytic oxidative cascade that combines a P450 monooxygenase in the peroxygenase mode with α‐hydroxyacid oxidase(s) was developed for the conversion of saturated fatty acids into α‐ketoacids and resulted in the internal recycling of the oxidant H2 O2 . Overall, the O2 ‐dependent cascade relies on catalytic amounts of H2 O2 and releases water as the sole by‐product.